An Unusual Prepatellar Bursa Swelling: Patellar Button Dissociation and Migration - Thomas Hester; Farid Moftah (Case Reports in Orthopedics)
Implant loosening is not a new phenomenon, nor is implant migration; however they are rarely seen after knee arthroplasty surgery. Complications with patellar buttons have been reported before with peg failure, loosening, and patella fracture; however extra-articular migration is extremely rare. We report an unusual case of patellar button migration 11 years after total knee arthroplasty to the prepatellar bursa.